Microbiological and physicochemical treatments applied to metallurgic industry aiming water reuse - Bello, Antonio Roberto Crystal [UNESP]; Angelis, Dejanira de Franceschi de [UNESP]; Domingos, Roberto Naves [UNESP] (Brazilian Archives of Biology and Technology, 2008)
Estudou-se o reuso de água de um sistema composto por estação de tratamento de esgoto (ETE) com aeração prolongada e lodo ativado, e em uma estação compacta de tratamento de água (ECTA) de uma indústria metalúrgica. Os processos para obtenção da água de reuso foram: microbiológico e físico-químico. O esgoto doméstico foi bombeado para a ETE, onde houve formação de flocos biológicos e água clarificada. Avaliou-se a eficiência do processo microbiológico da ETE mediante a remoção de demanda bioquímica de oxigênio (DBO), demanda química de oxigênio (DQO) e sólidos sedimentáveis (SS). A eficiência do processo físico-químico de clarificação e desinfecção foi avaliada mediante análises de pH, turbidez, cor, contagem de bactérias heterotróficas aeróbias, cloro livre, dureza, alcalinidade, cloretos, sulfatos, sólidos totais dissolvidos (STD). Na água de reuso além desses parâmetros avaliou-se a toxicidade aguda ao microcrustáceo Daphnia similis.

A study was conducted on the reuse of the water in a system composed of a sewage treatment plant (STP) using prolonged aeration with activated sludge and a compact water treatment plant (CWTP) in a metallurgic industry. The processes for obtaining the water for reuse were microbiological and physicochemical. The domestic sewage was then pumped to the STP, where biological flocks were formed and clarified water was obtained. The efficiency of the microbiological process in the STP was evaluated for removal of biochemical oxygen demand (BOD), chemical oxygen demand (COD) and sedimentary solids (SS). The efficiency of physicochemical processes for clarifying the water and disinfection was evaluated through analysis of pH, turbidity, color, aerobic heterotrophic bacterial count, free chlorine, hardness, alkalinity, chlorides, sulfates and dissolved total solids (DTS). In the reuse of the water, acute toxicity for the microcrustaceans Daphnia similis was also evaluated.
Keywords: Water; reuse; sewage; microorganisms; disinfection